EFEKTIVITAS KINERJA PEGAWAI DALAM PELAYANAN PUBLIK DI DESA KONDANGJAYA - , Natalia Aryati; Hanny Purnamasari; Indra Aditya (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
ABSTRACT This research examines effectiveness related to employee performance in Kondangjaya Village. This research aims to determine the effectiveness of employee performance in Kondangjaya Village in public services. In measuring the effectiveness of employee performance in Kondangjaya Village, Richard and M. Steers’ theory is used, namely elements of self-adaptation, elements of work performance and elements of job satisfaction. The method used in this research is qualitative, with data collection techniques through observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results show that the effectiveness of employee performance in public services in Kondangjaya Village is quite good overall, and its application in work can be considered successful, but there are still several aspects that need to be improved. in optimizing employee performance and adequate facilities. In this way, the performance of employees in Kondangjaya Village can be made more effective.